(untitled) (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background: Stunting is a condition in which a child experiences growth and development disorders due to lack of nutritional intake for a long time. The First 1000 Days of a baby’s life can prevent stunting Mothers’ perspectives and understanding of the first 1000 days are crucial in preventing stunting. Objective : to ascertain the relationship In Suka Damai Village, Hinai District, Langkat Regency, a pregnant mother’s knowledge and attitude toward the first 1000 days of life with stunting prevention. Method : analytical survey research with design study Which used is cross sectional . Population study This is Mother pregnant who checks Her pregnancy . The population is 40 people and with technique total sampling . Instrument use questionnaire and techniques data analysis using analysis chi square . Results : Most of the twenty-three individuals knew enough. (32.5%), the majority is positive (26, or 65.0%), the minority is good (four, or 10.0%), and the attitude is negative (only 14, or 35.0%). In Peaceful Village, Hinai District, there is a correlation between pregnant women’s attitudes throughout the first 1000 days of life and their ability to prevent stunting (p-value = 0.000; p<0.05) Conclusion : In Suka Damai Village, Hinai District, there is information about the attitude of pregnant mothers during the first 1000 days of life and how to prevent stunting. It is advised to try to learn more about mothers’ 1000-day life spans in order to prevent stunting